Contrasting Actions of Endothelin ET(A) and ET(B) Receptors in Cardiovascular Disease - Schneider, Markus P. (2007)
First identified as a powerful vasoconstrictor, endothelin has an extremely diverse set of actions that influence homeostatic mechanisms throughout the body. Two receptor subtypes, ET(A) and ET(B), which usually have opposing actions, mediate the actions of endothelin. ET(A) receptors function to promote vasoconstriction, growth, and inflammation while ET(B) receptors produce vasodilation, increases in sodium excretion, and inhibit growth and inflammation. Potent and selective receptor antagonists have been developed and have shown promising results in the treatment of cardiovascular diseases such as pulmonary arterial hypertension, acute and chronic heart failure, hypertension, renal failure and atherosclerosis. However, results are often contradictory and complicated because of the tissue-specific vasoconstrictor actions of ET(B) receptors and the fact that endothelin is an autocrine and paracrine factor whose activity is difficult to measure in vivo. Considerable questions remain regarding whether ET(A) selective or non-selective ET(A)/ET(B) receptor antagonists would be useful in a range of clinical settings.